2012
DOI: 10.1155/2012/396232
|View full text |Cite
|
Sign up to set email alerts
|

Early Oral Ovalbumin Exposure during Maternal Milk Feeding Prevents Spontaneous Allergic Sensitization in Allergy-Prone Rat Pups

Abstract: There are conflicting data to support the practice of delaying the introduction of allergenic foods into the infant diet to prevent allergy development. This study investigated immune response development after early oral egg antigen (Ovalbumin; OVA) exposure in a rat pup model. Brown Norway (BN) rat pups were randomly allocated into groups: dam reared (DR), DR pups challenged daily (days 4–13) with oral OVA (DR + OVAc), DR pups challenged intermittently (on day 4, 10, 12, and 13) with oral OVA (DR + OVAi), fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…When the antigen was changed from OVA to the readily absorbable human gamma globulins (HGG; 1 mg/g), the mice developed tolerance [38] but they developed an immune response if HGG dose was reduced to 0.1 µg/g. Penttila et al (2012) fed rat pups 1 mg OVA intermittently or daily from day 4 after birth until day 13 [39]. Regardless of the dosing regimen, they determined that dam-reared pups produced low levels of circulating OVA-specific IgE and IgG1 and they suggest that early daily OVA exposure may prevent early allergic sensitization [39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the antigen was changed from OVA to the readily absorbable human gamma globulins (HGG; 1 mg/g), the mice developed tolerance [38] but they developed an immune response if HGG dose was reduced to 0.1 µg/g. Penttila et al (2012) fed rat pups 1 mg OVA intermittently or daily from day 4 after birth until day 13 [39]. Regardless of the dosing regimen, they determined that dam-reared pups produced low levels of circulating OVA-specific IgE and IgG1 and they suggest that early daily OVA exposure may prevent early allergic sensitization [39].…”
Section: Resultsmentioning
confidence: 99%
“…Penttila et al (2012) fed rat pups 1 mg OVA intermittently or daily from day 4 after birth until day 13 [39]. Regardless of the dosing regimen, they determined that dam-reared pups produced low levels of circulating OVA-specific IgE and IgG1 and they suggest that early daily OVA exposure may prevent early allergic sensitization [39]. These data are in excellent agreement with our preliminary work which showed that pups fed 1 mg OVA or higher for up to 2 weeks responded with oral tolerance (referred to in Section 3.1).…”
Section: Resultsmentioning
confidence: 99%
“…However, because of the high morbidity and mortality of HRV associated diarrhea in developing countries and among immunesuppressed patients, the potential risk of sensitizing these patients to egg during infancy or an episode of frequently fatal gastroenteritis must be balanced against their potential benefit as determined by appropriate clinical trials [61] . Alternatively, the administration of chicken IgY Abs to breast fed children may be of less concern, since important immune molecules such as TGF-β present in human maternal milk has been shown to be a strong anti-allergenic factor inducing oral tolerance to dietary antigens in neonates [62] . Finally, IgY Abs have been used in randomized, placebo-controlled clinical trials carried out by Sarker et al and by Rahman et al in hospitalized children.…”
Section: Discussionmentioning
confidence: 99%
“…Although several dietary interventions in this model have shown their immunomodulatory activity in young-adult animals [ 121 ], very few studies have focused on earlier periods of life [ 122 ]. For example, this rat strain is also suitable for studying how diet can modulate spontaneous allergic sensitization when the early oral allergen exposure is performed during maternal milk feeding [ 123 ]. Therefore, this model can also be used to ascertain the dietary modulation of the development of oral tolerance in early life.…”
Section: Immunomediated Pathologies In Early Rat Lifementioning
confidence: 99%